Patient Perspectives on Smoking Cessation and Interventions in Rheumatology Clinics. Issue 3 (27th February 2020) - Wattiaux, Aimée; Bettendorf, Brittany; Block, Laura; Gilmore‐Bykovskyi, Andrea; Ramly, Edmond; Piper, Megan E.; Rosenthal, Ann; Sadusky, Jane; Cox, Elizabeth; Chewning, Betty; Bartels, Christie M.
Abstract : Objective: Although smoking is a risk factor for cardiovascular and rheumatic disease severity, only 10% of rheumatology visits document cessation counseling. After implementing a rheumatology clinic protocol that increased tobacco quitline referrals 20‐fold, we undertook this study to examine patients' barriers and facilitators to smoking cessation based on prior rheumatology experiences, to solicit reactions to the new cessation protocol, and to identify patient‐centered outcomes or signs of cessation progress following improved care. Methods: We recruited 19 patients who smoke (12 with rheumatoid arthritis [RA] and 7 with systemic lupus erythematosus [SLE]) to participate in 1 of 3 semistructured focus groups. Transcripts of the focus group discussions were analyzed using thematic analysis to classify barriers, facilitators, and signs of cessation progress. Results: Participant‐reported barriers and facilitators to cessation involved psychological, health‐related, and social and economic factors, as well as health care messaging and resources. Commonly discussed barriers included viewing smoking as a crutch amid rheumatic disease, rarely receiving cessation counseling in rheumatology clinics, and very limited awareness that smoking can worsen rheumatic diseases or reduce efficacy of some rheumatic disease medications. Participants endorsed our cessation protocol with rheumatology‐specific education and accessible resources, such as a quitline. Beyond quitting, participants prioritized knowing why and how to quit as signs of progress outcomes. Conclusion: Focus groups identified themes and categories of facilitators/barriers to smoking cessation at the levels of patient and health system. Two key outcomes of improving cessation care for patients with RA and SLE were knowing why and how to quit. Emphasizing rheumatologic health benefits and cessation resources is essential when designing and evaluating rheumatology smoking cessation interventions.